2015
DOI: 10.1021/jp5100389
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Modulation of Backbone Conformation and Intermolecular Distance of Conjugated Polymers Toward Understanding the Dynamism of π-Figuration of their Conjugated System

Abstract: Continuous tuning of the backbone conformation and interchain distance of a π-conjugated polymer is an essential prerequisite to unveil the inherent electrical and optical features of organic electronics. To this end, applying pressure in a hydrostatic medium or diamond anvil cell is a facile approach without the need for side-chain synthetic engineering. We report the development of high-pressure, time-resolved microwave conductivity (HP-TRMC) and evaluation of transient photoconductivity in the regioregular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 109 publications
1
19
0
Order By: Relevance
“…Fore xample, although the emission peak of bulk PThw as not changed before and after the addition of MeOH (Supporting Information, Figure S12), al arge blue-shift is observed when the PThcomposites were subjected to MeOH vapor (Figure 3a). [19] As the adsorption isotherm of MeOH for 1'PTh·5 shows as teep rise even in the low-pressure region, it demonstrates that the hybridization of functional polymers within porous materials is ak ey strategy for sensing systems intended to detect very low concentration of vapors (Supporting Information, Figure S15). Although the blue-shifting of the emission of polythiophene upon exposure to methanol is contradictory to what is observed for bulk PTh, it can be rationalized by the coordination of MeOH molecules to the open metal sites of 1,aphenomenon that is confirmed by single crystal analysis in analogous systems.…”
Section: Angewandte Chemiementioning
confidence: 98%
See 1 more Smart Citation
“…Fore xample, although the emission peak of bulk PThw as not changed before and after the addition of MeOH (Supporting Information, Figure S12), al arge blue-shift is observed when the PThcomposites were subjected to MeOH vapor (Figure 3a). [19] As the adsorption isotherm of MeOH for 1'PTh·5 shows as teep rise even in the low-pressure region, it demonstrates that the hybridization of functional polymers within porous materials is ak ey strategy for sensing systems intended to detect very low concentration of vapors (Supporting Information, Figure S15). Although the blue-shifting of the emission of polythiophene upon exposure to methanol is contradictory to what is observed for bulk PTh, it can be rationalized by the coordination of MeOH molecules to the open metal sites of 1,aphenomenon that is confirmed by single crystal analysis in analogous systems.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Raman spectra of 1'PTh·5 upon exposure to MeOH vapor shows as hift in the band at 1454 cm À1 to longer wavenumber,a nd can be attributed to al oss of planarity of the backbone (Supporting Information , Figure S14). [19] As the adsorption isotherm of MeOH for 1'PTh·5 shows as teep rise even in the low-pressure region, it demonstrates that the hybridization of functional polymers within porous materials is ak ey strategy for sensing systems intended to detect very low concentration of vapors (Supporting Information, Figure S15).…”
Section: Angewandte Chemiementioning
confidence: 98%
“…High pressure structural studies of π‐conjugated polymers are motivated by the fact that hydrostatic pressure enhances intermolecular interactions and changes intramolecular geometry without chemical changes. These experiments were pioneered by Mårdalen et al, who reported on the structural and optical transitions for polythiophenes, paving the way for polythiophene studies with fullerene derivatives . These studies were augmented by structural high pressure studies of polyphenylenes by Heimel et al and Gitsas et al, and by optical high pressure studies including studies of poly( p‐ phenylene vinylene) by Morandi et al and investigations of fluorene copolymers by Schmidtke et al Common to all these studies are planarization of otherwise twisted polymers followed by a redshift in photoluminescence (PL).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that in ODCB, polymer chains form 1D aggregates by several interchain π–π stacking (Figure e), in agreement with temperature‐dependent absorption spectra. The Kuhn length equals to the total length of sixteen repeating units of BDOPV‐2T, significantly larger than those of P3HT, indicating the rigidness of polymer backbone in ODCB solution, due to the intramolecular hydrogen bonding. The radius obtained from SANS fitting is comparable to the molecular modeling results of 28.5 Å.…”
mentioning
confidence: 98%